"Studying his analysis of the digital skills courses for Primary School in the Kingdom of Saudi Arabia in the light of the standards of the integrated curriculum "STEM - Alqahtani, Amsha Munahi (Journal of Curriculum and Teaching Methodology, 2022)
This study aimed to reveal the extent of the inclusion of digital skills books at the primary stage" upper grades "fourth, fifth and sixth primary, to the standards of the integrated curriculum" , and the researcher followed the descriptive analytical approach, and the study tool was represented in a list of standards of the integrated curriculum and card analysis of the content of: The field of "interpreting and linking information from science, technology, engineering and mathematics" at the first level by 56.6%, then the field of "learning the exact content of Science, Technology, Engineering and mathematics and its application" at the second level by 17.6%, then the field of "integrating the contents of Science, Technology, Engineering and mathematics" at the third level by 13.6%, then the field of "cooperation as a team(STEM)" at the fourth level by 6.3%, then the field of "Use and application of technology creatively and professionally" at the fifth level by 3.2%, and finally the field of "development of critical thinking among students" at the sixth level by 2.7%, at the sixth level by 2.7%, at the sixth level by 2.7 when the field of "engagement and preoccupation in the survey of global issues" was not available and received a percentage Based on the results, the researcher recommended rebuilding the digital skills books at the primary level and developing them in the light of the standards of the integrated curriculum, and holding workshops for teachers to introduce them to the integrated curriculum.